SIGNIFICANCE OF GROUNDWATER RESOURCES FOR PROVISION OF WATER CONSUMPTION IN VARNA DISTRICT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study highlights the significance of the groundwater resources in present state of water use in Varna District in the context of provision of essential needs and demands of the society and economic development. The household water supply in the Varna region sourced from groundwater over an eight-year period (2016–2023) is analysed. A primary trend identified in water consumption is the decrease in the volume of used groundwater. Household consumption represents a significant portion of the total water usage, predominantly concentrated in the city of Varna. Public water supply dominates, accounting for over 99% of the total water volume during the period under review. The overall reduction in water consumption is approximately 22.4%. Industrial water usage remains stable throughout the study period, with an upward trend observed in specific sectors such as the chemical and food processing industries. Agricultural consumption of freshwater from groundwater sources is also notable, particularly in cases of private water supply for irrigation of agricultural crops. The water use from private water supply in this sector fluctuate considerably, ranging from 1,367,245 m³ in 2016 to 2,040,130 m³ in 2023. Water consumption in Varna region shows significant seasonal variation. A general trend of water consumption indicates pronounced seasonal irregularities, with a sharp increase during the summer months, especially in resort areas and settlements with tourism development potential. The expansion of settlements, including the incorporation of new territories into urban planning and the reclassification of agricultural lands, has not been accompanied by adequate water supply infrastructure in recent years. This has hindered the provision of reliable water services to consumers. Sustainable management of groundwater resources and the optimization of their utilization will be the key to ensuring long-term water security in the region.